Strategi Pemasaran Program Pasar Amal Baitulmaal Munzalan Indonesia Cabang Pontianak (Jurnal Manajemen Bisnis Era Digital, 2026)
In this modern technological era, many organizations conduct fundraising activities through charity programs. One such organization is Baitulmaal Munzalan Indonesia, Pontianak Branch, which organizes a charity market program to collect funds or goods that can be used to help people obtain the items they need at affordable prices.This study aims to analyze the various marketing strategies used in the charity market program of Baitulmaal Munzalan Indonesia, Pontianak Branch. The research involved 10 informants, consisting of 1 employee of Baitulmaal Munzalan Indonesia, Pontianak Branch, and 9 consumers of the charity market. The researcher employed a qualitative research method by conducting a case study on the selected object. The data collection techniques used in this study included documentation, interview and observation. The purpose of this study was to identify the marketing strategies of the charity market program and to explore ways to improve them. The result of this research suggest that the charity market program applies seven marketing strategies, namely segmentation, targeting, positioning, promotion, place, product, and price. The marketing strategies of the charity market at Baitulmaal Munzalan Indonesia, Pontianak Branch, already cover many important aspects and demonstrate good potential. However, there are still some elements that need to be refined and added in order to make the strategies more effective and attract greater community participation